Germany's populist disruptors and the “politics of fluidity” - Lees, Charles (Frontiers in Political Science, 2025)
IntroductionThe German party system has become increasingly unstable as the “politics of centrality” that was associated with the old Federal Republic has succumbed to a new “politics of fluidity”. The subsequent process of political fragmentation has seen the emergence of populist challenger parties of right and left. The article focuses on the more significant strand of right-wing populism represented by the Alternative für Deutschland (AfD) but also considers the persistence of left populism in elements of the Linke and the recent breakaway Bündnis Sahra Wagenknecht (BSW).MethodsThe article uses mixed methods to explain modern German populism in comparative and historical perspective, and looking at demand and supply side factors, with a focus on party-based populism.ResultsThe article demonstrates that Germany's populist challengers have a strong impact on party competition but face significant systemic biases that limit their impact on government formation at the state level and certainly at the Federal level.DiscussionThe article concludes that ceteris paribus the possibility of a right-wing populist government at the national level in Germany is smaller than in European democracies with more majoritarian electoral and party systems such as France. Nevertheless, the emergence of Germany's populist disruptors presents a systemic challenge, not least because of the dangers of over-reaction from Germany's political and legal establishment to the rise of the AfD in particular.